2016
DOI: 10.1080/13557858.2016.1244621
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of negative health-care experiences and self-reported health behavior change in three racial and ethnic groups

Abstract: Objectives Our two study objectives were: (1) to understand the relationship between the perception of a previous negative health care experience and race/ethnicity, and how socio-demographic, access-to-health-care, and self-reported health variables modified this relationship and (2) to assess how many behaviors participants reported changing as a result of experiencing a perceived negative health care experience, which behaviors they changed, and if there were differences in patterns of change across racial/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Discriminatory treatment in healthcare settings is a well-documented barrier to receiving medical care ( Schwei et al, 2017 ; Trivedi & Ayanian, 2006 ). Individuals who perceive discrimination in the healthcare setting are less likely to have primary care doctors ( Blanchard & Nicole Lurie, 2004 ), voluntarily receive treatment, and have good overall mental and physical health ( Burgess et al, 2007 ; Hausmann et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Discriminatory treatment in healthcare settings is a well-documented barrier to receiving medical care ( Schwei et al, 2017 ; Trivedi & Ayanian, 2006 ). Individuals who perceive discrimination in the healthcare setting are less likely to have primary care doctors ( Blanchard & Nicole Lurie, 2004 ), voluntarily receive treatment, and have good overall mental and physical health ( Burgess et al, 2007 ; Hausmann et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to findings from another study and appeared to be a barrier in achieving good asthma control in children 45 . A previous study found the negative experience with healthcare provider influenced health-seeking behaviour 46 . Children should be reviewed for asthma even if the asthma is mild, as it could recur in adulthood, and childhood asthma is a risk factor for later developing pulmonary disease 47 .…”
Section: Discussionmentioning
confidence: 98%
“…This could signal that one's expectations adjust after a previous negative consultation at the same provider. In addition, such negative encounters have been shown to affect patients' behaviour outside the clinical setting (Bayuo 2017;Schwei et al 2016). For example, patients in Ghana have reported opting-out of care in their nearby and designated facilities due to negative experiences (Bayuo 2017).…”
Section: Discussionmentioning
confidence: 99%